Common miRNA Patterns of Alzheimer’s Disease and Parkinson’s Disease and Their Putative Impact on Commensal Gut Microbiota - Hewel, Charlotte; Kaiser, Julia; Wierczeiko, Anna; Linke, Jan; Reinhardt, Christoph; Endres, Kristina; Gerber, Susanne (Frontiers in Neuroscience, 2019)
With the rise of Next-Generation-Sequencing (NGS) methods, Micro-RNAs (miRNAs) have achieved an important position in the research landscape and have been found to present valuable diagnostic tools in various diseases such as multiple sclerosis or lung cancer. There is also emerging evidence that miRNAs play an important role in the pathogenesis of neurodegenerative diseases such as Alzheimer’s disease (AD) or Parkinson’s disease (PD). Apparently, these diseases come along with changes in miRNA expression patterns which led to attempts from researchers to use these small RNA species from several body fluids for a better diagnosis and in order to observe disease progression. Additionally, it became evident that microbial commensals might play an important role for pathology development and were shown to have a significantly different composition in patients suffering from neurodegeneration compared with healthy controls. As it could recently be shown that secreted miRNAs are able to enter microbial organisms, it is conceivable that the host’s miRNA might affect the gut microbial ecosystem. As such, miRNAs may inherit a central role in shaping the “diseased microbiome” and thereby mutually act on the characteristics of these neurodegenerative diseases. We have therefore 1) compiled a list of miRNAs known to be associated with AD and/or PD, 2) performed an in silico target screen for binding sites of these miRNA on human gut metagenome sequences and 3) evaluated the hit list for interesting matches potentially relevant to the etiology of AD and or PD. The examination of protein identifiers connected to bacterial secretion system, lipopolysaccharide biosynthesis and biofilm formation revealed an overlap of 37 bacterial proteins that were targeted by human miRNAs. The identified links of miRNAs to the biological processes of bacteria connected to AD and PD have yet to be validated via in vivo experiments. However, our results show a promising new approach for understanding aspects of these neurodegenerative diseases in light of the regulation of the microbiome.